VD_FINDINFO Jug / 2020 / 429 vom 29. Oktober 2019 - VD Tribunal cantonal (2019)
ANNONCE D'APPEL, DÉLAI, ABUS DE CONFIANCE, DÉFENSE D'OFFICE, PRÉSOMPTION D'INNOCENCE, LEASING | 138 CP, 10 CPP (CH), 132 CPP (CH), 399 al. 1 CPP (CH), 403 al. 1 let. a CPP (CH)